Recent Advances in Incretin-Based Pharmacotherapies for the Treatment of Obesity and Diabetes - Tan, Qiming; Akindehin, Seun E.; Orsso, Camila E.; Waldner, Richelle C.; DiMarchi, Richard D.; Müller, Timo D.; Haqq, Andrea M. (Frontiers in Endocrinology, 2022)
The incretin hormone glucagon-like peptide-1 (GLP-1) has received enormous attention during the past three decades as a therapeutic target for the treatment of obesity and type 2 diabetes. Continuous improvement of the pharmacokinetic profile of GLP-1R agonists, starting from native hormone with a half-life of 2–3 min to the development of twice daily, daily and even once-weekly drugs highlight the pharmaceutical evolution of GLP-1-based medicines. In contrast to GLP-1, the incretin hormone glucose-dependent insulinotropic polypeptide (GIP) received little attention as a pharmacological target, because of conflicting observations that argue activation or inhibition of the GIP receptor (GIPR) provides beneficial effects on systemic metabolism. Interest in GIPR agonism for the treatment of obesity and diabetes was recently propelled by the clinical success of unimolecular dual-agonists targeting the receptors for GIP and GLP-1, with reported significantly improved body weight and glucose control in patients with obesity and type II diabetes. Here we review the biology and pharmacology of GLP-1 and GIP, and discuss recent advances in incretin-based pharmacotherapies.